Perencanaan Jaringan Pipa di Perumahan THE OZ Kelurahan Karang Widoro Kecamatan Dau Kabupaten Malang Menggunakan Aplikasi Software WaterCAD V8i - Sihombing, Arion Frederick; Haribowo, Riyanto (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
The OZ Residence located in Karang Widoro urban village, Dau  sub-district, Malang district with a total construction of 250 housing unit.  Now, there is no water distribution network planning yet in The OZ Residence. The purpose of this study is findout the discharges needed to meet the needs of water in residence, knowing the planning of water distribution network, and make the budget plan, and determine the benchmark water price through the process of economic analysis. Simulation of water distribution network are using WaterCAD Program. Based on the calculation of the total discharge needed in the planning of water distribution network in the residence, the average discharge needed was 3.4 l/s. The simulation result using WaterCAD program has been fulfilled the standard. The budget plan of this plan is Rp. 359.856.800,00, So, the price of water price for Rp. 1.300,00/